PENGARUH RECEIVABLE TURNOVER DAN CASH TURNOVER TERHADAP RETURN ON ASSET PADA PERUSAHAAN HM .SEMPOERNA TBK - Roza Gustika, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
PT HM Sempoerna Tbk is a cigarette company which is able to win Market Leader in 2007 predicate, where the predicate previously has been attached to PT Gudang Garam Tbk since 1989. Return On Asset (ROA) is a ratio used to measure the ability of companies in using the overall assets to produce profit. This study aims to 1) find out partially how the effect of Receivable Turnover (RTO) on Return On Assets (ROA) 2) find out partially how the effect of Cash Turnover (CTO) on Return On Assets (ROA) 3) find out simultaneously how the effect of Receivable Turnover (RTO) and Cash Turnover (CTO) on Return On Asset (ROA) at PT HM Sempoerna Tbk period 2011-2016. Sample of this research is financial report of PT HM Sempoerna Tbk period 2011-2016 by using time series method. Method of data analysis is simple linear regression finding result Y = 0,223 + 0,001 X1 + 0,010 X2 + e show by Partial Receivable Turnover affects positive but insignificant 0.001 and significant rate 0.740 (> 0.05) and partially Cash Turnover has a positive but insignificant effect of 0.010 with significant rate 0.484 (> 0.05). Simultaneously Receivable Turnover (RTO) and Cash Turnover (CTO) have positive but insignificant effect with significant rate 0,316 (> 0,05). From the result of determination test it can be seen that coefficient of determination (Adjusted R ^ 2) obtained 0,536. It means that 53.6% Return On Assets (ROA) can be explained by the variable Receivable Turnover (RTO) and Cash Turnover (CTO), while for the rest of 47.4% Return On Assets (ROA) is influenced by other variables which are not discussed in this study.